(untitled) (International Journal of Built Environment and Sustainability, 2017)
Sustainable livable housing is pre-condition for healthy living, improve quality of life and critical to economic and social survival. It also encompasses various aspects that predominantly depend on economic, social, cultural and environmental (ESCE) conditions within the locality. To this end, this paper seeks to explore, classify and assess the sustainable livable housing attributes from the existing literatures through content analysis. A review of literature revealed a total of ninety two (92) constructs, which were further grouped nine (9) livable housing-related attributes groups. Well-structured questionnaires were administered to residents of traditional urban areas (TUA) of Iwo Osun State, Nigeria with ninety two (92) constructs on Likert scale. Data were analyzed using descriptive statistic and relative importance index (RII). Out of (92) constructs from nine (9) livable housing-related attributes groups, the results identified seventy eight (78) important attributes (i.e. 35 most important and 43 important) across groups and construct that TUA residents found important. Over RII was 0.409 for overall assessment of sustainable livable housing condition by TUA residents indicating that TUA residents are dissatisfied with their current housing conditions.